Pengaruh Pemberian Biskuit Dangke terhadap Status Gizi dan Perkembangan Kognitif Baduta Gizi Kurang - Masdalis; Andi Nurlinda; Nurhaedar Jafar (Nutrition Science and Health Research, 2022)
This study aims to anallyze the effect og giving dangke biscuits on head circumference, upper arm circumference, and cognitive development of undernourished children under two. The method used is experimental or experimental research (Experiment Research ) with an experimental research design used in this study with a random pretest-posttest with control group design. The results showed that both the experimental group and the control group used the T-Test (paired samples test). The experimental group had a significant effect, namely the pre-test-post-test increase in head circumference with a p 0,00 < α = 0,05 and cognitive development with a p –value of 0,003, and the pretest- posttest on the upper arm circumperence with a p –value of 0,0207.